Physeterostemon gomesii (Melastomataceae): the fourth species of this endemic genus in Bahia, Brazil - Amorim, André Márcio; Jardim, Jomar Gomes; Goldenberg, Renato (Phytotaxa, 2014)
Physeterostemon gomesii is described and illustrated. In addition, a map and a key to all four taxa of this genus are provided. This species can be distinguished from other Physeterostemon species by its non-rhizomatous shrubby habit, 5-merous flowers, 10 stamens, and 3-locular ovary.